Symposium 3: Phenomenology and networked learning - a found chord - Johnson, Mike; Healey-Benson, Felicity; Adams, Catherine; Bonderup Dohn, Nina; Goetz, Greta (Proceedings of the International Conference on Networked Learning, 2024)
Phenomenology has captured the imagination of researchers since Edmund Husserl (1859-1938) began to use the term. Examples of phenomenology within the networked learning conference proceedings are notable yet few, as examined by Healey-Benson (2020) and Johnson (2020) in the 12th Networked Learning Conference, and who then went on to form https://hanfod.NL . The goal to ‘engage the networked learning community in discussing the suitability of choosing phenomenology as a research methodology’ (Oberg and Bell 2012, p209) had been demonstrated by Dohn (2006) and continued by Adams (2014).